CORPORATE GOVERNANCE: A LITERATURE REVIEW WITH A FOCUS ON PUBLIC SECTOR UNDERTAKINGS IN INDIA - Vartak, Pallavi (PEOPLE: International Journal of Social Sciences, 2018)
Business dynamic of today’s market has changed and as a result, market need to focus on transparency in the business hence corporate governance has become important for all sectors including government organization. Corporate Governance is steadily focusing on building the confidence of its various stake holders including Customers, Suppliers, employees, shareholders, Bankers and Society at large. As these public-sector organization (PSU) are socially responsible unit, it becomes utmost important for these organization to adhere to these clauses because these are run by tax payer money for its operation. A company is directed and controlled with the system of rules, practices and process of the corporate governance. The corporate Governance framework of any Public-Sector Undertakings depends upon the four pillars namely Transparency, Full disclosures, Independent monitoring and Fairness to all. Study examines the existing corporate Governance environment, practice and institutional framework in PSUs in India. It is a theoretic review of corporate governance of PSU in India. This paper attempts to understand the various reason for failure to hold governance of the PSUs in India and accordingly provide the solutions to improve the implementation of corporate governance. Though the public sector has unique characteristics but need to adhere the corporate governance to bring the accountability, transparency in business and enhance confidence of the stakeholders. This paper is based on purely secondary research from the various literature available in the journal. It is purely conceptual paper based on the authors recommendations.